Complicaciones clínicas relacionadas con la nutrición en pacientes adultos con diabetes mellitus del Centro de Salud Bypass, Ciudad de Babahoyo, periodo octubre 2019-marzo 2020. - Dueñas Villamarin, Ingrid Verónica (2020)
The research carried out at the Bypass Health Center in the city of Babahoyo investigates the clinical complications presented by people with diabetes mellitus problems, which are generated by inadequate feeding or resistance to adherence to non-pharmacological treatment, which It includes eating habits and lifestyle in general. Currently, people who suffer from a public health disease such as diabetes, have problems in the control of food intake and cause various complications such as Retinopathy, Nephropathy, Diabetic Foot, Hyperglycemia, among others, for this reason the objective of The research consists in determining how nutrition influences the presence of diseases derived from diabetes. The methodology of the investigative process is integrated by the deductive and inductive methods, because they allow a particular analysis of the data obtained on the analyzed variables, in addition the types of field, transversal and applied research are applied, since the study is carried out in a certain period; where direct contact is established with the sources of information that, through the application of the frequency of consumption, 24-hour reminder and survey techniques help in obtaining relevant information that allows correlating the research variables. The results obtained reveal that patients with diabetes mellitus do not follow balanced diets according to their characteristics or state of health which generate the conditions conducive to the appearance of medical complications.